Parasite specific 7SL-derived small RNA is an effective target for diagnosis of active trypanosomiasis infection. - Stephen M Chiweshe; Pieter C Steketee; Siddharth Jayaraman; Edith Paxton; Kyriaki Neophytou; Heidi Erasmus; Michel Labuschagne; Anneli Cooper; Annette MacLeod; Finn E Grey; Liam J Morrison (Public Library of Science (PLoS), 2019)
Human and animal African trypanosomiasis (HAT & AAT, respectively) remain a significant health and economic issue across much of sub-Saharan Africa. Effective control of AAT and potential eradication of HAT requires affordable, sensitive and specific diagnostic tests that can be used in the field. Small RNAs in the blood or serum are attractive disease biomarkers due to their stability, accessibility and available technologies for detection. Using RNAseq, we have identified a trypanosome specific small RNA to be present at high levels in the serum of infected cattle. The small RNA is derived from the non-coding 7SL RNA of the peptide signal recognition particle and is detected in the serum of infected cattle at significantly higher levels than in the parasite, suggesting active processing and secretion. We show effective detection of the small RNA in the serum of infected cattle using a custom RT-qPCR assay. Strikingly, the RNA can be detected before microscopy detection of parasitaemia in the blood, and it can also be detected during remission periods of infection when no parasitaemia is detectable by microscopy. However, RNA levels drop following treatment with trypanocides, demonstrating accurate prediction of active infection. While the small RNA sequence is conserved between different species of trypanosome, nucleotide differences within the sequence allow generation of highly specific assays that can distinguish between infections with Trypanosoma brucei, Trypanosoma congolense and Trypanosoma vivax. Finally, we demonstrate effective detection of the small RNA directly from serum, without the need for pre-processing, with a single step RT-qPCR assay. Our findings identify a species-specific trypanosome small RNA that can be detected at high levels in the serum of cattle with active parasite infections. This provides the basis for the development of a cheap, non-invasive and highly effective diagnostic test for trypanosomiasis.